Analisis peran perbankan dan inflasi di sektor perdagangan dalam mendorong pertumbuhan ekonomi masyarakat - Nafiah, Novia Maslihatun; Himmati, Risdiana; Sobir, Labib Muzaki; Indraswari, Kesy (Journal of Economics Research and Policy Studies, 2024)
The economic growth of communities in the trade sector in Indonesia is influenced by various factors, including the role of Islamic banking. This study aims to analyze the influence of Islamic banking on community economic growth, focusing on the variables of Capital Adequacy Ratio, Financing to Deposit Ratio, Non-Performing Loan, and inflation from 2018-2023. The research method used is panel data regression. Data analysis used panel data regression to measure the relationship between capital adequacy ratio, financing to deposit ratio, non-performing loans, inflation, and gross domestic product (GDP). Data were obtained from reports from the Financial Services Authority (OJK) and the Central Statistics Agency. The results show that the Capital Adequacy Ratio, Financing to Deposit Ratio, and Non-Performing Loan individually do not significantly impact economic growth in the trade sector, while inflation has a significant effect. This study emphasizes that inflation has an important role in understanding the impact of Islamic banking on economic growth in the trade sector. The results of this study indicate that controlling inflation strengthens the contribution of Islamic banking in driving community economic growth.